RANCANG BANGUN SISTEM INFORMASI PEMESANAN WEDDING ORGANIZER BERBASIS WEBSITE - yefilina_gulo_id yefilina; Supriyono Diana Laily Fitri; Supriyono (LPPM Universitas Abdurrab, 2026)
Wedding Organizer services assist in planning and organizing wedding events. At Gemilang Wedding Organizer Kudus, the ordering and data management processes were previously handled manually, causing inefficiencies in transaction recording, scheduling, and payment monitoring. This study aims to design and develop a web-based wedding organizer ordering information system to improve service efficiency and data management. The system development method applied is the Waterfall model, consisting of requirements analysis, system design, implementation, and testing. The system was developed using the Laravel framework with a MySQL database. Main features include wedding package catalog, online ordering, payment proof upload, transaction verification, event scheduling management, and transaction reporting. Black Box testing results indicate that all system functions operate according to specified requirements. Furthermore, User Acceptance Testing demonstrates a high level of user acceptance, indicating that the system is feasible and capable of supporting operational activities while improving service quality at Gemilang Wedding Organizer Kudus.